2014
DOI: 10.12659/msm.890468
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of sIgA, histatin-5, and lactoperoxidase levels in saliva of adolescents with dental caries

Abstract: BackgroundSaliva contains a number of protective factors such as mucins, immunoglobulins (e.g., IgA, IgG, and IgM), and enzymes (e.g., lysozyme and lactoperoxidases) that play an important role in the maintenance of oral health. The aim of this study was to compare levels of sIgA, histatin-5, and lactoperoxidase in saliva of adolescents with dental caries.Material/MethodsThirty-five adolescents (age 18 years) from high school were examined. Eight subjects with DMF=3 (Group I) and 27 adolescents with DMF>11 (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
4
26
1
1
Order By: Relevance
“…According to the analysis of the current study results, increasing the number of decayed teeth (particularly between the groups 1 and 4) significantly increased the amount of salivary IgA, which was consistent with the results of the studies by Fidalgo ( 4 ), Ranadheer ( 2 ), Gornowicz ( 6 ), Bagherian ( 8 ) and yang ( 9 ). These studies also indicated the higher levels of salivary IgA in the cases with dental caries, compared with caries free ones.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the analysis of the current study results, increasing the number of decayed teeth (particularly between the groups 1 and 4) significantly increased the amount of salivary IgA, which was consistent with the results of the studies by Fidalgo ( 4 ), Ranadheer ( 2 ), Gornowicz ( 6 ), Bagherian ( 8 ) and yang ( 9 ). These studies also indicated the higher levels of salivary IgA in the cases with dental caries, compared with caries free ones.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, there is a strong tendency toward using saliva to diagnose diseases in the early stages ( 12 , 13 ); in addition, using saliva is an easy and cost-effective method, it is safe and non-invasive for the examiner, and also it does not need extensive equipment and facilities( 4 , 14 , 15 ). There are a few and inadequate studies on adult’s salivary IgA and only the studies by Koga-ito ( 3 ) and Gornowicz ( 6 ) involved adults. Therefore, investigation in this regard seemed to be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results are consistent with the results of Gornowicz et al, who demonstrated increased level of HST-5 in group of children with severe caries, but higher concentrations were observed in children with severe form of the disease compared to patients with the initial demineralization involvement [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, histatins 1, 3, and 5 belong to a family of salivary peptides that help to maintain the human oral mucosa, along with the β-defensins. An elevated expression of histatin 5 is detected in the saliva of children with a high level of dental cavities harboring specific bacterial species, such as Streptococcus mutans, S. sanguinis, S. mitis, as well as Lactobacillus rhamnosus in the oral environment [77,78]. In contrast, RNAse 7 is abundantly found within specialized uroepithelial cells in bladder lining, ureters, and kidneys, protecting the urinary system from invading microbes.…”
Section: Other Host Antimicrobial Peptidesmentioning
confidence: 99%